Regression of traits-other-than-production phenotypes for cows milked once a day on estimated breeding values obtained from cows milked twice a day - Sneddon N; Lopez-Villalobos N; Garrick DJ; Rocha JF; Donaghy D (The New Zealand Society of Animal Production (Inc), 2019)
The use of traits other than production (TOP) to aid selection for conformation fit-for-purpose offspring becomes more important as once-a-day (OAD) milking for whole or part season becomes more common. In 2013 Massey University Dairy 1 farm transitioned their mixed-breed herd milked twice a day (TAD) to an OAD spring-calving system. All cows on the farm were scored for 14 inspector TOP traits and four farmer-scored traits for a total of 1,163 records over five seasons (168 to 254 cows per year). The scores were adjusted for age of the cow and season. The adjusted phenotypes for all cows for each trait were then regressed on their corresponding nationally-produced TAD estimated breeding values (EBV), which had been calculated without using these phenotypes. The four farmer-scored traits had the lowest relationships with EBV. Estimates of regression coefficients near one were observed for the udder traits (udder support, rear udder, front teats, udder overall), dairy conformation and body capacity. This supports the use of national EBVs in OAD herds derived mostly from records on daughters in TAD herds.